Fatal Myocarditis following COVID-19 mRNA Immunization: A Case Report and Differential Diagnosis Review - Sousa, Pedro Manuel Barros de; Silva, Elon Almeida; Campos, Marcos Adriano Garcia [UNESP]; Lages, Joyce Santos; Corrêa, Rita da Graça Carvalhal Frazão; Silva, Gyl Eanes Barros (MDPI, 2024)
Carditis in childhood is a rare disease with several etiologies. We report a case of infant death due to pericarditis and myocarditis after the mRNA vaccine against COVID-19 (COVIDmRNAV). A 7-year-old male child received the first dose of the COVIDmRNAV and presented with monoarthritis and a fever non-responsive to oral antibiotics. The laboratory investigation showed signs of infection (leukocytosis, high levels of c-reactive protein). His condition rapidly deteriorated, and the patient died. The autopsy identified pericardial fibrin deposits, hemorrhagic areas in the myocardium, and normal valves. A diffuse intermyocardial inflammatory infiltrate composed of T CD8+ lymphocytes and histiocytes was identified. An antistreptolysin O (ASO) dosage showed high titers. The presence of arthritis, elevated ASO, and carditis fulfills the criteria for rheumatic fever. However, valve disease and Aschoff’s nodules, present in 90% of rheumatic carditis cases, were absent in this case. The temporal correlation with mRNA vaccination prompted its inclusion as one of the etiologies. In cases of myocardial damage related to COVID-19mRNAV, it appears to be related to the expression of exosomes and lipid nanoparticles, leading to a cytokine storm. The potential effects of the COVID-19mRNAV must be considered in the pathogenesis of this disease, whether as an etiology or a contributing factor to a previously initiated myocardial injury.
Keywords: cathecolamin-induced cardiotoxicity; COVID-19; immunization; mRNA vaccine; multisystem inflammatory syndrome; myocarditis; rheumatic heart disease